WORKSHOP PEMANFAATAN INTERNET UNTUK SUMBER BELAJAR BAHASA INGGRIS DALAM MENINGKATKAN KINERJA GURU SD DI KECAMATAN DANAU TELUK KOTA JAMBI - Munawwaroh, Khidayatul; Dewi, Sri; Mayasari, Mayasari; Silfia, Efa; Wahyuni, Uli (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
The need to apply science and technology is becoming an increasingly important need. For educators, the need for mastery of technology is something that must be mastered to support the learning process. The aim of this program is to equip elementary school teachers with mastery of using the Internet to facilitate the search for English learning resources and to introduce and deepen their knowledge of English learning aid sites to improve teacher performance. There are five stages in implementing a community service program to find English learning resources in Internet Usage Seminars: Introduction Stage, Social and Audience Stage, Development Stage, Internet usage training and final assessment stage. The conference lasted for two days. The first day of activity is in the form of material procurement. The second day focused on Internet usage practices. Keywords: internet workshop, teacher, english, learning resources